The Spillover Effect among CET Market, Coal Market, and New Energy Market for Dual-Carbon Target: New Evidence from China - Feng-Wei Gao; Yi-Min Wu; Ding Chen; Meng-Yao Hu (Discrete Dynamics in Nature and Society)
The spillover effect of the energy markets and the CET plays an important role in guiding the realization of two-carbon target; using the network spillover methodology of Diebold, Yilmaz, Jozef Barunı´k, and Toma´sKrehlı´k, we examine both the static and dynamic connectedness of CO2 emissions trading (CET) market, steam coal market, new energy, and traditional energy market in China from early Dec 2013 to the end of July 2021. At last, we verified the stability of the model and obtained the following findings: (1) the total spillover effect index is 13.91% between those markets, and it is mainly focused on short term. Moreover, the dynamic spillover effect is time-varying, and it is greatly influenced by the domestic and international environment; (2) the connectedness of the CET market with other energy markets is neutral, the development of new energy market is strong, it is the main transmitter to other markets, especially to the traditional energy market except for the steam coal market, and the coal market is an effect transmitter. These results provide a theoretical reference for investors and policy makers who are concerned with the return connectedness among the CET market, new energy market, and steam coal market in China.